Estrategias metodológicas en el área de lengua y literatura y su influencia en el proceso de enseñanza–aprendizaje en los estudiantes de 3ro de Educación Básica de la Unidad Educativa Emigdio Esparza Moreno - Mendoza Reyes, Deysi Nicole (2023)
Methodological strategies are techniques that allow learning to be constructed and must be organized through the facilitation of significant experience for the student's development. The present case study developed in the first semester of 2023 regarding the methodological strategies in the area of language and literature and its influence on the teaching-learning process in the 3rd year of basic education students of the Emigdio Esparza Moreno educational unit of the province of the rivers of the Babahoyo canton. Once the data was obtained from the interview applied to the teachers and the evaluation of the students, it was possible to identify the strategies and methodologies used in the teaching and learning process. By identifying them, it was possible to establish the relationship between the two and determine that these strategies positively influence student learning. That is to say, they have worked, however, through 100% results. Only 76% master reading while 66% master writing. Therefore, it is necessary to innovate, update and improve these strategies with the clear objective of achieving a class where all students master 100% reading and writing skills and in turn reach the required learning levels according to their age and academic period.